Hommage aan Karel Geirlandt. - Hoet, Jan; de Vree, Freddy (Antwerpen : Galerie Campo, 1990)
Bijl, Guillaume ; Bogart, Bram ; Broodthaers, Marcel ; Brusselmans, Jean ; Burssens, Jan ; Copers, Leo ; Cortier, Amédée ; Cox, Jan ; de Cordier, Thierry ; De Keyser, Raoul ; Fontaine, Jean de la ; Delvoye, Wim ; De Smet, Gust ; D'Haese, Roel ; Dierickx, Karel ; Drybergh, Charles ; Duchateau, Hugo ; Elias, Etienne ; Fabre, Jan ; Geirlandt, Toni ; Gentils, Vic ; Haveman, Nina ; Heirman, Rony ; Joostens, Paul ; Lafontaine, Marie-Jo ; Leblanc, Walter ; Maet, Marc ; Maeyer, Marcel ; Mara, Pol ; Matthys, Danny ; Mortier, Antoine ; Pacquée, Ria ; Panamarenko ; Peire, Luc ; Permeke, Constant ; Raveel, Roger ; Roobjee, Pjeroo ; Servranckx, Victor ; Spilliaert, Léon ; Swennen, Walter ; Van Anderlecht, Englebert ; Van Breedam, Camiel ; Vandenberg, Philip ; van den Berghe, Frits ; Vandercam, Serge ; Van Gestel, Fik ; Van Hoeydonck, Paul ; Van Rafelghem, Paul ; Van Severen, Dan ; Vercruysse, Jan ; Verheyen, Jef ; Vertessen, Liliane ; Vlerick, Pierre ; Wittevrongel, Roger ; Wyckaert, Maurice
Nederlands & Frans
Hommage aan Karel Geirlandt, Galerie Campo, Antwerpen, 09 - 24.02.1990
boek